ASSA13-10-9 Overexpressing Cellular Repressor of E1A-Stimulated Genes Promote Hypoxia-Induced VEGF Paracrine Via HIF-1α in Mesenchymal Stem Cells. (29th April 2013) - Chengfei, Peng; Yaling, Han; Xiaoxiang, Tian; Jie, Deng; Chenghui, Yan; Jie, Wang
Abstract : Background: Hypoxia inducible factor-1α (HIF-1α) is the key transcription regulator for multiple angiogenic factors, including vascular endothelial growth factor (VEGF). Cellular repressor of E1A-stimulated genes (CREG) has also been identified a potent promoter of angiogenesis. However, the mechanisms by which CREG promotes angiogenesis are not fully understood. Here, we show that CREG is an effective stimulator of HIF-1α under hypoxia in bone marrow-derived mesenchymal stem cells (BMSCs). Methods: All experiments were performed on rat BMSCs. The level of VEGF was measured by ELISA. The HIF-1α mRNA was analysed by RT-PCR. The level of HIF-1α protein and the mechanisms mediating these proangiogenic effects were determined by Western blotting. Results: We found that VEGF release from BMSCs was significantly increased in parallel with high level of HIF-1α in BMSCs following anoxia or hypoxia in time-dependent manner. Furthermore, the level of VEGF released from BMSCs overexpressing CREG and the expression of HIF-1α in BMSCs overexpressing CREG were higher than the normal BMSCs under hypoxia. Rather, HIF-1α steady-state mRNA was also affected by CREG. This effect was associated with constitutive activation of phosphatidylinositol 3-kinase (PI3K)/Akt and its effector p70 S6 kinase (p70 S6K ), but not extracellular-signal regulated kinase 1/2. The use of small molecule inhibitors LY294002 or rapamycin to inhibit PI3K/Akt and p70 S6K activities, respectively, resulted in diminished HIF-1α activation and subsequent VEGF expression. RNA interference-mediated knockdown of HIF-1α suppressed CREG-induced VEGF synthesis and angiogenic tube formation, confirming that the effect was HIF-1α specific. Conclusions: Overexpressing CREG promotes hypoxia-induced VEGF paracrine via HIF-1α in mesenchymal stem cells. Therefore, CREG could play a major role in angiogenesis and vascular remodelling.